On the robustness of minimum wage effects: Geographically-disparate trends and job growth equations - John T. Addison; McKinley L. Blackburn; Chad D. Cotti (IZA Journal of Labor Economics, 2015)
Recent attempts to incorporate spatial heterogeneity in minimum-wage employment models have been targeted for using overly simplistic trend controls and for neglecting the potential impact of wage minima on employment growth. This paper investigates whether such considerations call into question findings of statistically insignificant employment effects reported in the literature for an archetypal low-wage sector in the United States: restaurants and bars. Understanding this relationship goes to the heart of the policy debate surrounding minimum wages and, hence, is critical to investigate carefully. Our results conclude that a focus on employment levels is appropriate for this sector and, further, that the deployment of nonlinear trend controls does not dislodge prior research which finds weak support for the existence of adverse minimum-wage employment effects on employment.
Keywords: J23; J38; 330; Minimum wages; Employment; Employment change; Spatial controls